2012
DOI: 10.1684/ecn.2012.0303
|View full text |Cite
|
Sign up to set email alerts
|

Contact with stimulated T cells up-regulates expression of peptidylarginine deiminase 2 and 4 by human monocytes

Abstract: The antigenic targets of the rheumatoid arthritis (RA)-associated autoantibodies to "citrullinated" proteins are generated following citrullination by a peptidylarginine deiminase (PAD). Of the five PAD isotypes, two-PAD2 and PAD4-are expressed in RA synovial tissue. Within this tissue, the activation of macrophages and fibroblasts mediated by T-cell contact or driven by cytokines plays a prominent part in the pathogenesis. We wanted to determine whether cytokine stimulation and contact with T cells could play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…No mRNA or protein of any PAD isotype was detected in resting or stimulated synovial fibroblasts. Thus, they suggested that contact between stimulated T cells and monocytes/macrophages or cytokine-activated monocytes−/macrophages constitutes a highly likely source of PADI2 and PADI4, which are observed in inflamed synovial tissues [37]. Calabrese et al.…”
Section: Discussionmentioning
confidence: 99%
“…No mRNA or protein of any PAD isotype was detected in resting or stimulated synovial fibroblasts. Thus, they suggested that contact between stimulated T cells and monocytes/macrophages or cytokine-activated monocytes−/macrophages constitutes a highly likely source of PADI2 and PADI4, which are observed in inflamed synovial tissues [37]. Calabrese et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is as yet unknown how osteoclast lineage cells may be affected by the costimulation system in a similar manner to professional APCs. That costimulation molecules influence the activation state of not only T cells but also APCs (17) suggests that the crosstalk between T cells and osteoclasts may go beyond the expression of pro-and anti-osteoclastogenic cytokines (5,7,18,19). Most importantly, the engagement of CD80/86 expressed on the surface of osteoclast lineage cells may constitute a mechanism by which the differentiation state of osteoclast linage cells could be regulated in a physiological manner by the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, increased protein expression of PADI2 during the differentiation of monocytes to macrophages using PBMCs from RA patients and controls were reported [13]. The expression of PADI2 and PADI4 was found to increase in human monocytes after being stimulated by activated T cells [14]. We believe that the increased PADI expression during the differentiation of macrophage could lead to citrullination of certain proteins, and resulting in inflammatory responses.…”
Section: Introductionmentioning
confidence: 57%